Correlates of colorectal cancer screening among residents of Ohio Appalachia - Paskett, Electra D. (2013)
There is an excess burden of colorectal cancer (CRC) in the Appalachian region of the U.S., which could be reduced by increased uptake of CRC screening tests. Thus, we examined correlates of screening among Appalachian residents at average-risk for CRC. Using a population-based sample, we conducted interviews with and obtained medical records of Appalachian Ohio residents 50–75 years between September 2009 and April 2010. Using multivariable logistic regression, we identified correlates of being within CRC screening guidelines by medical records. About half of participants were within CRC screening guidelines. Participants who were older (OR=1.04, 95% CI: 1.01, 1.07), had higher income ($30,000–$60,000, OR=1.92, 95% CI: 1.29, 2.86; ≥$60,000, OR=1.80, 95% CI: 1.19, 2.72), a primary care provider (OR=4.22, 95% CI: 1.33, 13.39), a recent check-up (OR=2.37, 95% CI: 1.12, 4.99), had been encouraged to be screened (OR=1.57, 95% CI: 1.11, 2.22), had been recommended by their doctor to be screened (OR=6.68, 95% CI: 3.87, 11.52), or asked their doctor to order a screening test (OR=2.24, 95% CI: 1.36, 3.69) had higher odds of being screened within guidelines in multivariable analysis. Findings suggest that access to and utilization of healthcare services, social influence, and patient-provider communication were the major factors associated with CRC screening. Researchers and healthcare providers should develop and implement strategies targeting these barriers/facilitators to improve CRC screening rates and reduce the CRC burden among residents of Appalachia.